Base-catalysed [3 + 2] cycloaddition of propargylamines and aldehydes to substituted furans. Issue 3 (18th January 2018) - Shen, Jinhai; Zhao, Jing; Hu, Bing; Chen, Yangxin; Wu, Longqiao; You, Qihua; Zhao, Li
Abstract : A base-catalysed [3 + 2] cycloaddition reaction using propargylamines as allenyl anion equivalents for the regiospecific synthesis of substituted furans under metal-free conditions is developed. Abstract : A base-catalysed [3 + 2] cycloaddition reaction of propargylamines and aldehydes for the regiospecific synthesis of substituted furans under metal-free conditions is developed. Propargylamines are used as allenyl anion equivalents and applied in [3 + 2] cycloaddition reactions with aldehydes. Various substituted furans are provided up to 91% yield for 28 examples.